Autocracies at critical junctures: a model for the study of dictatorial regimes - Merkel, Wolfgang; Gerschewski, Johannes (2011)
Abstract: "How can authoritarianism in an age of democratization survive? What are the critical junctures when a dictatorship becomes less stable and potentially fails? In a project funded by the German Research Foundation (DFG), three pillars of stability of autocratic rule are identified: legitimacy, co-optation, and repression. Referring to historical institutionalism's key concept of critical juncture, the hypothesis is based on the observation that these junctures become regime threatening when a serious crisis in one pillar occurs and the two other pillars can no longer sufficiently compensate this instability." (author's abstract)